The Dynamic Aspects of Smart Contract in Non-Fungible Tokens - Qonita Nadya Haq; Aimee Aurilya Anindita; Erina Setyowati; Putri Liny Anggraini (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Technological advances always lead to various implications in people's lives, not least in the aspect of buying and selling transactions. In the current era, the dynamics of buying and selling transactions are enlivened by the presence of Non-Fungible Tokens (NFT); as an asset embodied in the form of a digital token. Furthermore, one of the components of NFT is the existence of smart contracts; as the presence of smart contracts also raises legal issues. This legal research aims to examine and examine the problems of smart contracts when they become evidence in a dispute; while at the same time reviewing the validity of smart contracts in the positive legal system in Indonesia. This legal research uses primary legal materials and secondary legal materials with a conceptual approach and legislation. The results of this study state that there is no legal instrument that regulates smart contracts, so the implementation of smart contracts is legal under Indonesian law. On the other hand, the existence of a smart contract as a form of an agreement is subject to the enforcement of Article 1320 of the Civil Code, so that the smart contract fulfills the components of the agreement as required in the legislation